Commercial honey in the Philippines I. pollen grains analysis - Tilde, Aurora C. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 1992)
Seventy-two samples of honey collected from all over the country were subjected to pollen grain analysis. About 50 kinds of pollen grains were identified. Pollen grains frequency analysis indicated 14 predominant types, 8 secondary types, and 14 minor types. In general, Mimosa pudica L., Cocos nucifera L., and Myrtaceae and Compositae species are the most important nectar sources as inferred by the overall predominance of their pollen types in the honey samples.